Telemedicine : Guidelines in India and its Importance in COVID Pandemic - Vikas Gurbani; Shagun Thakur (Indian Journal of Forensic Medicine & Toxicology, 2021)
Social Distancing became the new norm in the COVID 19 pandemic. While at one side the world-widemedical fraternity is finding ways to combat the viral infection, there were patients with existing illness whoneeded follow-up care. The role of Telemedicine became important under such circumstances.A study conducted by Earnst & Young (EY) in association with Indian Pharmaceutical Alliance (IPA)[Mar’20], estimated the Telemedicine market in India to reach $5.5 billion By 2025[3]. These telemedicinecompanies offer services like teleconsultation, e-prescription, e-pharmacy and online ordering & schedulingof laboratory investigations.Just after the start of statutory lockdown in India in view of COVID pandemic, on 25 March’2020, theBOARD OF GOVERNORS in supersession of the Medical Council of India notified the “TelemedicinePractice Guidelines” to enable R.M.P.s to provide healthcare using Telemedicine [7]. [This constitutesAppendix 5 of the Indian Medical Council (Professional Conduct, Etiquette and Ethics Regulation, 2002]Although the practice of Telemedicine was going on in some form or the other in the last two decades, butthere was a question with respect to its legitimacy and acceptance by the medical fraternity at large. Thenotification of these guidelines has cleared the picture to a large extent and lays the foundation for this newtool of medicine practice.This article is a peak into the current guidelines of Telemedicine in India and its usefulness in the COVIDpandemic.